Repeated genetic divergence plays a minor role in repeated phenotypic divergence of lake-stream stickleback. (8th December 2022) - Poore, Hilary A; Stuart, Yoel E; Rennison, Diana J; Roesti, Marius; Hendry, Andrew P; Bolnick, Daniel I; Peichel, Catherine L
Abstract: Recent studies have shown that the repeated evolution of similar phenotypes in response to similar ecological conditions (here "parallel evolution") often occurs through mutations in the same genes. However, many previous studies have focused on known candidate genes in a limited number of systems. Thus, the question of how often parallel phenotypic evolution is due to parallel genetic changes remains open. Here, we used quantitative trait locus (QTL) mapping in F2 intercrosses between lake and stream threespine stickleback ( Gasterosteus aculeatus ) from four independent watersheds on Vancouver Island, Canada to determine whether the same QTL underlie divergence in the same phenotypes across, between, and within watersheds. We find few parallel QTL, even in independent crosses from the same watershed or for phenotypes that have diverged in parallel. These findings suggest that different mutations can lead to similar phenotypes. The low genetic repeatability observed in these lake-stream systems contrasts with the higher genetic repeatability observed in other stickleback systems. We speculate that differences in evolutionary history, gene flow, and/or the strength and direction of selection might explain these differences in genetic parallelism and emphasize that more work is needed to move beyond documenting genetic parallelism to identifying the underlying causes.